2021
DOI: 10.1016/j.ekir.2021.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 Study of Roxadustat to Treat Anemia in Non–Dialysis-Dependant CKD

Abstract: Introduction: Roxadustat is an oral hypoxia-inducible factor prolyl hydroxylase inhibitor that has demonstrated safety and efficacy versus placebo in phase III trials in patients with anemia of chronic kidney disease (CKD) who were not on dialysis (NDD).Methods: This was a phase III, active-controlled, multicenter, partially randomized, open-label study in Japanese patients with NDD CKD. Patients who had used recombinant human erythropoietin or darbepoetin alfa (DA) before conversion were randomized to roxadus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…Study 1517-CL-0310 26 was a multicenter, partially randomized (nonrandomized reference group is described subsequently), DA-controlled, open-label study conducted in Japan from January 2017 to March 2020 (ClinicalTrials.gov: NCT02988973 ). In this study, NDD patients with CKD previously treated with recombinant human erythropoietin or DA were randomized to initially receive roxadustat 3 times weekly for 52 weeks or DA once every 2 weeks for 24 weeks, whereas NDD patients with CKD who had previously used epoetin beta pegol were assigned to receive roxadustat 3 times weekly for 52 weeks (reference group); the reference group was not included in this ophthalmologic analysis ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study 1517-CL-0310 26 was a multicenter, partially randomized (nonrandomized reference group is described subsequently), DA-controlled, open-label study conducted in Japan from January 2017 to March 2020 (ClinicalTrials.gov: NCT02988973 ). In this study, NDD patients with CKD previously treated with recombinant human erythropoietin or DA were randomized to initially receive roxadustat 3 times weekly for 52 weeks or DA once every 2 weeks for 24 weeks, whereas NDD patients with CKD who had previously used epoetin beta pegol were assigned to receive roxadustat 3 times weekly for 52 weeks (reference group); the reference group was not included in this ophthalmologic analysis ( Figure 1 b).…”
Section: Methodsmentioning
confidence: 99%
“…In phase 3 studies, roxadustat has been found to have efficacy and safety in achieving and maintaining Hb target levels in DD 20 , 21 , 22 , 23 and NDD 24 , 25 , 26 patients with CKD with anemia. Specifically, 2 Japanese phase 3 studies have revealed the efficacy of roxadustat in maintaining Hb within 10.0 to 12.0 g/dl in DD (study 1517-CL-0307) 20 and NDD 26 patients with CKD with anemia whose Hb levels were previously maintained with ESAs; in both studies, roxadustat was found to be noninferior to DA.…”
mentioning
confidence: 99%
“…All published phase II trials indicate that HIF-PHI therapy is at least as efficacious as conventional ESA therapy in managing Hb levels in both nondialysis-dependent CKD (ND-CKD and dialysis-dependent (DD-CKD) patients [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. The meta-analysis of 26 randomized controlled trials involving 2804 patients with CKD comparing the use of HIF-PHIs versus ESAs or placebo in the treatment of renal anemia found HIF-PHIs superior to placebo and at least as efficacious as classic ESAs in the short term [ 5 ].…”
Section: Hypoxia-inducible Factor Inhibitorsmentioning
confidence: 99%
“…Regarding safety, HIFs also activate, additionally to EPO, a large number of genes, which can also cause beneficial effects. Potential clinical benefits of HIF-PHIs therapy include: achieving Hb target with a 5–17-fold lower plasma EPO levels relative to those receiving ESA; and a lipid-lowering effect, blood-pressure reduction, anti-inflammatory effects, protection from ischemic injuries, and protective effects with regard to CKD [ 5 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Roxadustat and daprodustat are demonstrated to reduce triglyceride, total cholesterol, and low-density lipoprotein levels [ 62 , 63 , 69 , 71 ].…”
Section: Hypoxia-inducible Factor Inhibitorsmentioning
confidence: 99%
“…[3][4][5][6][7] Several phase III clinical trials have verified the efficacy and safety of roxadustat as a therapy for anemia in nondialysis-dependent and dialysis-dependent patients. 5,[8][9][10][11] Of note, previous phase II and III trials indicated the dose-effect relationship of roxadustat and correction of anemia, 6,12 where Hb levels rapidly increased by approximately 10 g/l within the first 4 to 5 weeks with a weight-based initial dose, that is, 1.5 to 2 mg/kg 3 times per week. 6,7,13 This phenomenon in turn explained why the mean weekly dose of roxadustat was reduced after 4 weeks of treatment in some dialysis-dependent recipients with 100 to 110 g/l of Hb at baseline, indicating dose reduction due to Hb overshooting.…”
mentioning
confidence: 99%